Respuesta :

To solve 1-20, you plug in the number for the variable that the variable is equal to e.i. a) x = -3 so you plug -3 in every place there is an x

-2(-3)^2 - 3(-3) + 1

-2(9) +9 + 1

-18 +10

-8
The solution to a) is -8.

Please leave a comment and let me know if you also need help with b-d or if you understand.

Answer:

a) -8

b) -56

c) 3

d) 6

Step-by-step explanation:

(a). The expression is given by,

[tex]\Rightarrow -2x^2-3x+1[/tex]

Now, substitute the the value of x = 3 in the expression

[tex]\Rightarrow -2\times(-3)^2-3\times(-3)+1[/tex]

[tex]\Rightarrow -8[/tex]

(b). The expression is given by,

[tex]\Rightarrow 8-(3x-2)^2[/tex]

Now, substitute the the value of x = -2 in the expression

[tex]\Rightarrow 8-(3\times(-2)-2)^2[/tex]

[tex]\Rightarrow -56[/tex]

(c). The expression is given by,

[tex]\Rightarrow \dfrac{-3}{k+2}[/tex]

Now, substitute the the value of k = -3 in the expression

[tex]\Rightarrow \dfrac{-3}{-3+2}[/tex]

[tex]\Rightarrow 3[/tex]

(d). The expression is given by,

[tex]\Rightarrow \dfrac{15m}{n+1}-m^2+n[/tex]

Now, substitute the the value of m = 1 and n = 2 in the expression

[tex]\Rightarrow \dfrac{15\times1}{2+1}-1^2+2[/tex]

[tex]\Rightarrow 6[/tex]

Hence, This is the required solution.

ACCESS MORE